Islam dan Persoalan Higiene di Hindia Belanda - Jaelani, Gani Achmad (Jurnal Sejarah, 2017)
This research seeks to elaborate the question of hygiene in its relation with the Islamic doctrine in Netherlands-Indie. In the colonial world, hygiene is inevitably related to the colonial politic in order to assure the well-being of the population and the good health of the workers. A number of projects since the mid-19th century, such as the creation of Dokter Djawa School in 1851 and the programme of vaccination, were the indicator of the attempt to improve the health status of the population, along with the hygiene program in the plantation to assure the health status of the workers. Physicians who were dealing with this question frequently encountered difficulties in socializing the idea of hygiene. Since the majority of the population was moslem, they were trying to use the Islamic doctrine which is in line with the principle of hygiene in their propaganda. This article will try to analyze how the physicians used the Islamic doctrine in their works; how physicians treat the image of Islam as a religion from a medical point of view.